Influence of polarization of free-electron system in semiconductor on the position of minimum in plasma light reflection - Severin, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The dielectric permeability of the free-electron system in semiconductor is
usually considered using the Drude-Lorentz model without taking into account this
system polarization. But it seems reasonable to include polarization phenomena into
consideration of the free-electron system behavior. In this paper, the position of
minimum in plasma optical reflection by the system of free electrons is analyzed with
allowance for this system polarization. This position can substantially differ from that
given via calculation of it within the framework of the traditional Drude-Lorentz model.
This difference is significant when analyzing the available experimental results.